THE TRANSLATION SHIFT AND ACCURACY ANALYSIS OF MUSEUM MACAN’S CAPTION - Deny, Deny (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2018)
Museum MACAN is the first museum that exhibit modern art. Museum MACAN has Indonesia-English caption in their Instagram account in order to promote their collection. This study investigates translation shift occurs in Museum MACAN’s Instagram caption and the accuracy of their translation. The translation shift is used to produces accurate translation. This study uses Catford’s theory about translation shift (1964) and the accuracy based on ATA Rubric Assessment. The data were twenty five Museum MACAN’s Instagram captions. The collected data were analysed, in order to fine the translation shift and accuracy of their caption. There are three evaluators to rate the accuracy of the captions. The first evaluator is the writer of this study; the second evaluator is a student of management from Universitas Negeri Jakarta who works as freelance translator more than two years, the third evaluator is a professional translator who has been in translation field for twenty five years. The result of the translation shift analysis is there are five shifts occur in Museum MACAN’s Instagram captions. The most used shift is structure shift. It shows that the use of shift helps writer or translator adjusts word into appropriate sentence from source text to target text.